Follow the steps to solve the system of linear equations by using the elimination method:
(i) Multiply the given equation by suitable constant so as to make the coefficients of the variable to be eliminated equal.
(ii) Add the new equations obtained if the terms having the same coefficient are opposite signs and subtract if they are of the same sign.
(iii) Solve the equation thus obtained.
(iv) Substitute the value found in any one the given equations.
(v) Solve it to get the value of the other variable.
Worked-out examples on elimination method:
1. Solve the system of equation 2x + y = -4 and 5x – 3y = 1 by the method of elimination.
Solution:
The given equations are:
2x + y = -4 …………… (i)
5x – 3y = 1 …………… (ii)
Multiply equation (i) by 3, we get;
{2x + y = -4} …………… {× 3}
6x + 3y = -12 …………… (iii)
Adding (ii) and (iii), we get;
or, x = -11/11
or, x = -1
Substituting the value of x = -1 in equation (i), we get;
2 × (-1) + y = -4
-2 + y = -4
-2 + 2 + y = -4 + 2
y = -4 + 2
y = -2
Therefore, x = -1 and y = -2 is the solution of the system of equations 2x + y = -4 and 5x – 3y = 1
2. Solve the system of equation 2x + 3y = 11, x + 2y = 7 by the method of elimination.
Solution:
The given equations are:
2x + 3y = 11 …………… (i)
x + 2y = 7 …………… (ii)
Multiply the equation (ii) by 2, we get
{x + 2y = 7} …………… (× 2)
2x + 4y = 14 …………… (iii)
Subtract equation (i) and (ii), we get
Substituting the value of y = 3 in equation (i), we get
2x + 3y = 11
or, 2x + 3 × 3 = 11
or, 2x + 9 = 11
or, 2x + 9 – 9 = 11 – 9
or, 2x = 11 – 9
or, 2x = 2
or, x = 2/2
or, x = 1
Therefore, x = 1 and y = 3 is the solution of the system of the given equations.
3. Solve 2a – \(\frac{3}{b}\) = 12 and 5a + \(\frac{7}{b}\) = 1
Solution:
The given equations are:
2a – \(\frac{3}{b}\) = 12 …………… (i)
5a + \(\frac{7}{b}\) = 1 …………… (ii)
Put \(\frac{1}{b}\) = c, we have
2a – 3c = 12 …………… (iii)
5a + 7c = 1 …………… (iv)
Multiply equation (iii) by 5 and (iv) by 2, we get
10a – 15c = 60 …………… (v)
10a + 14c = 2 …………… (vi)
Subtracting (v) and (vi), we get
or, c = \(\frac{58}{-29}\)
or, c = -2
But \(\frac{1}{b}\) = c
Therefore, \(\frac{1}{b}\) = -2 or b = -\(\frac{1}{2}\)
Subtracting the value of c in equation (v), we get
10a – 15 × (-2) = 60
or, 10a + 30 = 60
or, 10a + 30 - 30= 60 - 30
or, 10a = 60 – 30
or, a = \(\frac{30}{10}\)
or, a = 3
Therefore, a = 3 and b = - \(\frac{1}{2}\) is the solution of the given system of equations.
4. x/2 + 2/3 y = -1 and x – 1/3 y = 3
Solution:
The given equations are:
x/2 + 2/3 y = -1 …………… (i)
x – 1/3 y = 3 …………… (ii)
Multiply equation (i) by 6 and (ii) by 3, we get;
3x + 4y = -6 …………… (iii)
3x – y = 9 …………… (iv)
Solving (iii) and (iv), we get;
or, y = -15/5
or, y = -3
Subtracting the value of y in (ii), we get;
x - 1/3̶ × -3̶ = 3
or, x + 1 = 3
or, x = 3 – 1
or, x = 2
Therefore, x = 2 and y = -3 is the solution of the equation.
x/2 + 2/3 y = -1 and x - y/3 = 3
● Simultaneous Linear Equations
Solvability of Linear Simultaneous Equations
Word Problems on Simultaneous Linear Equations
Word Problems on Simultaneous Linear Equations
Practice Test on Word Problems Involving Simultaneous Linear Equations
● Simultaneous Linear Equations - Worksheets
Worksheet on Simultaneous Linear Equations
Worksheet on Problems on Simultaneous Linear Equations
8th Grade Math Practice
From Elimination Method to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Mar 02, 24 05:31 PM
Mar 02, 24 04:36 PM
Mar 02, 24 03:32 PM
Mar 01, 24 01:42 PM
Feb 29, 24 05:12 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.